2008
DOI: 10.4067/s0716-078x2008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the American mink Mustela vison and its potential impact on the native fauna of Navarino Island, Cape Horn Biosphere Reserve, Chile

Abstract: Invasive exotic species of mammalian predators represent a major cause of vertebrate animal extinctions on islands, particularly those that lack native mammalian carnivores. In 2001, the American mink (Mustela vison) was recorded for the first time on Navarino Island, in the Cape Horn Biosphere Reserve (55° S) in Chile, representing the southernmost population of mink worldwide. In order to assess its potential impact on native fauna, we studied its diet on Navarino Island, as part of an integrative management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
3
30
2
7
Order By: Relevance
“…We found that coastal mink on Tierra del Fuego ate mammals and fish at similar frequencies, whereas Schüttler et al (2008) reported that mink on the north coast of Navarino Island (south of the Beagle Channel), consumed prey in descending order from mammals, birds, fish and crustaceans (Table 3). These differences could fruitfully be explored by systematic study of larger samples, in relation to prey availability, on both sides of the Beagle Channel.…”
Section: Agreement Of Results With Other Studiesmentioning
confidence: 44%
See 3 more Smart Citations
“…We found that coastal mink on Tierra del Fuego ate mammals and fish at similar frequencies, whereas Schüttler et al (2008) reported that mink on the north coast of Navarino Island (south of the Beagle Channel), consumed prey in descending order from mammals, birds, fish and crustaceans (Table 3). These differences could fruitfully be explored by systematic study of larger samples, in relation to prey availability, on both sides of the Beagle Channel.…”
Section: Agreement Of Results With Other Studiesmentioning
confidence: 44%
“…The same anxiety concerns the likelihood of their colonisation of other islands of the Fuegian Archipelago currently free of terrestrial carnivores. Mink have already crossed the Beagle Channel from Tierra del Fuego to parts of the Cape Horn Biosphere Reserve, specifically Hoste Island (Anderson et al 2006) and Navarino Island (Rozzi and Sherrifs 2003), where their summer diet is heavily dependent on native birds (Schüttler et al 2008;Ibarra et al 2009). …”
Section: Agreement Of Results With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuentes: (1) Arróniz-Crespo et al 2014;Jofre et al 2010, Lewis et al 2014aMéndez, 2013;Méndez et al 2013;Rozzi et al 2008b; (2) Mansilla et al 2012Mansilla et al , 2013aMansilla et al , 2014aOjeda et al 2014Ojeda et al , 2015; (3) Contador et al 2012Contador et al , 2014; (4) Merino et al 2008;Reyes et al 2015;(5) Crego et al 2014(5) Crego et al , 2015Ibarra et al 2009Ibarra et al , 2010Schüttler et al 2008Schüttler et al , 2009Schüttler et al , 2010Schüttler et al , 2011Jiménez et al 2014;(6) Berghöfer et al 2008(6) Berghöfer et al , 2010Jax & Rozzi, 2004;Rozzi & Schüttler, 2013;Rozzi, 2004, Rozzi et al 2006a,b, 2007, 2012a; (7) Aguirre, 2015; Ibarra et al 2012;Massardo et al 2012;Poole et al 2013;Rozzi 2012aRozzi ,b, 2013Rozzi et al 2010bRozzi et al ,c, 2014Rozzi et al , 2015(8) Medina, 2013;Pizarro & Caballero, 2011;Sherriffs et al 2005;Zárraga et a...…”
Section: Programa De Investigación Transdisciplinaria Del Parque Etnounclassified